Development of functional extruded snacks by utilizing paste shrimp (Acetes spp.): process optimization and quality evaluation. (7th November 2017) - Kumar, Raushan; Xavier, KA Martin; Lekshmi, Manjusha; Dhanabalan, Vignaesh; Thachil, Madonna T; Balange, Amjad K; Gudipati, Venkateshwarlu
Abstract: BACKGROUND: Functional extruded snacks were prepared using paste shrimp powder (A cetes spp.), which is rich in protein. The process variables required for the preparation of extruded snacks was optimized using response surface methodology. Extrusion temperature (130–144 °C), level of Acetes powder (100–200 g kg −1 ) and feed moisture (140–200 g kg −1 ) were selected as design variables, and expansion ratio, porosity, hardness, crispness and thiobarbituric acid reactive substance value were taken as the response variables. RESULTS: Extrusion temperature significantly influenced all the response variables, while Acetes inclusion influenced all variables except porosity. Feed moisture content showed a significant quadratic effect on all responses and an interactive effect on expansion ratio and hardness. Shrimp powder incorporation increased the protein and mineral content of the final product. The extruded snack made with the combination of extrusion temperature 144.59 °C, feed moisture 178.5 g kg −1 and Acetes inclusion level 146.7 g kg −1 was found to be the best one based on sensory evaluation. CONCLUSION: The study suggests that use of Acetes species for the development of extruded snacks will serve as a means of utilization of Acetes as well as being a rich source of proteins for human consumption, which would otherwise remain unexploited as a by‐catch. © 2017 Society of Chemical Industry